E.T.A. Hoffmanns »Kater Murr« Neue Lektüren - Liebrand, Claudia; Neumeyer, Harald; Wortmann, Thomas (Texturen, 2022)
With the 'Lebens-Ansichten des Katers Murr nebst fragmentarischer Biographie des Kapellmeister Johannes Kreisler in zufälligen Makulaturblättern' (1819/1921), E.T.A. Hoffmann, the author, composer, illustrator and legal scholar, created a piece of writing that can be considered one of the most groundbreaking novels of the 19th century. This volume assembles new readings that examine Hoffmann's Kater Murr from comparative, musicological and theatre theory perspectives. It also explores poetological (for Kater Murr that means consistently focusing on the materiality of its artistic production) as well as media-aesthetic and cultural studies approaches. With contributions by Prof. Dr. Lutz Ellrich, Prof. Dr. Achim Geisenhanslüke, Dr. Irmtraud Hnilica, Dr. Vanessa Höving, Prof. Dr. Claudia Liebrand, Prof. Dr. Christine Lubkoll, Prof. Dr. Frederike Middelhoff, Prof. Dr. Harald Neumeyer, Prof. Dr. Marion Schmaus, Prof. Dr. Monika Schmitz-Emans, Dagmar Wahl and Prof. Dr. Thomas Wortmann.